Visualisasi Topologi Routing pada Jaringan berdasarkan OSPF Link State Database - Amalia Miftakhul Jannah; Achmad Basuki (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
A computer network is a system consisting of several devices connected to each other to exchange data and information. One way to organize the network is by using routing protocol, which is a set of rules that determines how data packets can be sent from one device to another. OSPF (Open Shortest Path First) is one of the commonly used routing protocols in computer networks. In this final project, we will discuss about the visualization of routing topology in a network based on the link state database (LSDB) of OSPF. LSDB is a database that stores information about the network topology, which is used by OSPF to determine the best path for data packets to be sent using the Dijkstra algorithm. To visualize the routing topology, a web application will be created that can display the network topology graphically. This web application will use LSDB as a data source and will display the routing paths determined by OSPF. This application can be used to help network administrators understand the existing network topology, thus helping to organize and manage the network more effectively. In addition, visualization of routing topology can also help in analyzing and finding problems that occur in the network. The implementation results show the success of representing the OSPF's LSDB in a graphical visualization that forms a network topology of nodes and edges.